Photocataltic propertirs of zeolite-based materials for gegradation of methyl orange - Yılmaz, Özge. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Novel photocatalytic materials have been prepared by incorporation of TiO2 on ZSM-5 surface and incorporation of Y2O3, La2O3 and Ce2O3 on TiO2-ZSM-5 matrix. These materials have been characterized using scanning electron microscopy with energy dispersive X-ray (SEM-EDAX) spectroscopy, X-ray diffractometer (XRD), surface area analyzer (BET) and atomic force microscopy (AFM). The photocatalytic activity of the materials in UV light has been evaluated for degradation of methyl orange (MeO) selected as a model recalcitrant azo dye. SEM(EDAX) images reveal formation of unordered and non-uniform aggregates with certain TiO2 and metal-oxide percentages. All supported catalysts prepared at 400°C exhibit only anatase phase. The particle size of TiO2 increases either with temperature or with incorporation onto the ZSM-5 surface. Effects of various parameters are examined in the degradation process of MeO. 40 weight (wt) per cent TiO2 and 0.28 atomic (at) per cent metal ion loadings are used as optimum values in the final catalyst configurations. Effect of pH is examined both in the dark conditions and under irradiation. Acidic pH values show better adsorption capacities and also degradation efficiencies. Kinetics of MeO photodegradation in the presence of metal oxide loaded supported catalysts are followed by the application of Langmuir-Hinshelwood model. Heat-treated catalysts show low performances due to the presence of rutile phases. A mechanism is postulated for MeO degradation and a rough model is proposed for the adsorption of TiO2 and metal oxide species on the surface of ZSM-5. Finally, performances of all supported catalysts are compared with those of bare TiO2 prepared by sol-gel method and commercially available catalyst (Degussa P-25).
Keywords: Zeolites.; Titanium dioxide.